Tingkat Asupan Makronutrien dan Gaya Hidup terhadap Risiko terjadinya Obesitas di Lima Provinsi di Indonesia - Sirly Eka Nur Intan; Nurheni Sri Palupi; Endang Prangdimurti (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2022)
The problem of obesity is increasing in developed and developing countries. This study aims to analyze data on sociodemographic, consumption behavior, lifestyle, macronutrient intake, and adequacy of nutrition on the prevalence of obesity in adults based on secondary data from RISKESDAS 2013 and SKMI 2014 for the 19–55-year age group in the provinces of North Sulawesi, DKI Jakarta, East Kalimantan, West Papua, and North Sumatra. The relationship of obesity factors was analyzed by bivariate analysis, the risk factors of obesity were analyzed by multivariate analysis, and the level of macronutrients adequacy refers to recommended dietary allowances for adults. Results showed that sociodemographic factors, consumption behavior, and lifestyle were associated significantly with obesity. Sufficient consumption of fruits (at least 5 servings/day for 7 days/week) reduced the risk by 0.957 times. Consumption of energy (1759.22 kcal/ person/day), protein (77.82 g/person/day), and fat (52.49 g/person/day) in obese adults was higher than in normal adults (1690.14 kcal/person/day; 68.80 g/person/day; 45.34 g/person/day). The intake of protein (p = 0.018) and fat (p = 0.002) also the adequacy of protein (p = 0.015) in obese and normal adults showed significant differences.